ESPOCH´s Education, Management and Research Achievements in Sustainable Development - Byron Vaca; Magdy Echeverría; Rafael Cordova (Journal of Sustainability Perspectives, 2021)
Although sustainable development focuses on continuing the progress of societies without putting future resources and the environment at risk, new technologies, political treaties and economic initiatives are not enough. In this context, the role of universities is fundamental in the formation of leaders that allow raising awareness in society, and in the implementation of pilot projects that can be quickly adjusted and scaled. ESPOCH forms sustainability competencies with a formal focus, by including courses in environmental sustainability within all study curricula, as well as with a non-formal focus through extracurricular activities such as tree planting, avoiding the use of private vehicles, among others. Regarding management, projects such as the replacement of campus luminaires with high-efficiency LED lights, reducing energy consumption from 69 kWh-day to 11.5 KWh-day and the construction of intelligent buildings that will allow efficient management of resources and spaces are being carried out. The feedback obtained from ESPOCH’s participation in UI GreenMetric World University Rankings has allowed the university leaders, professors and students to identify the sectors that should be addressed as a priority and propose solutions to them considering sustainable development approaches.